Twenty Years of Science in the Public Interest: A History of the Congressional Science and Engineering Fellowship Program. - Filner, Bob (Isis: A Journal of the History of Science in Society)
Reviewed: Twenty Years of Science in the Public Interest: A History of the Congressional Science and Engineering Fellowship Program. Stine, Jeffrey K.